갱년기 여성의 생활스트레스가 생활만족도와 우울에 미치는 영향 - 박영미(Young-Mee Park); 신창식(Chang-Sik Shin) (한국콘텐츠학회 논문지, 15(5), 2015)
This study was done for analyzing the effects of menopausal women's life stress on life satisfaction and depression. The subjects of this study were 425 menopausal women in Daejeon Metropolitan City and Chungnam Province. Data were analyzed using descriptive statistics, t-test, ANOVA, Scheffe's test, Pearson correlation coefficients and stepwise multiple regression with the SPSS 19.0 program. Life stress differed according to marital status, income, climacteric symptoms level. Also the findings indicate that there is a significant positive correlation between life stress and life satisfaction. However, there is negative effect of life stress on depression. The results of this study offer basic data for the development of counseling and social support program to reduce depression and improve the life satisfaction for menopausal women. Also integrated programs and capacity-building programs were suggested to prepare the elderly life. 이 연구에서는 갱년기여성의 생활스트레스가 생활만족도와 우울에 미치는 영향을 분석해보았다. 연구대상자들은 대전광역시와 충청남도에 거주하는 425명의 갱년기 여성들이고, 자료는 SPSS 19.0을 통해 기술통계, t-test, ANOVA, Scheffe's test, 상관분석, 그리고 다중회귀분석을 통해 분석되었다. 자료의 분석결과 갱년기 여성의 생활스트레스는 결혼상태, 월수입, 월경상태 등의 수준에 따라 다르게 나타났다. 아울러 갱년기 여성의 생활스트레스와 생활만족도 간에는 유의미한 정적 관계가 나타났다. 반면에 갱년기 여성은 생활스트레스가 우울에는 부적 영향을 미치는 유의한 상관관계가 있는 것으로 나타났다. 이러한 연구결과를 통해 갱년기 여성의 생활만족도를 향상시키고 우울을 낮추기 위한 실천적 방안으로 사회적 지지와 상담 및 통합프로그램 제공과 함께 노년기 준비를 위한 역량강화 프로그램의 제공을 제언하고자 한다.